2020
DOI: 10.1093/intqhc/mzaa079
|View full text |Cite
|
Sign up to set email alerts
|

Variation between hospitals and reviewers in detection of adverse events identified through medical record review in Korea

Abstract: Objectives This study utilized the method of medical record review to determine characteristics of adverse events that occurred in the inpatient units of hospitals in Korea as well as the variations in adverse events between institutions. Design A two-stage retrospective medical record review was conducted. The first stage was a nurse review, where two nurses reviewed medical records of discharged patients to determine if scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
2
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 25 publications
1
16
2
4
Order By: Relevance
“… 19 A recent study using record reviews reported an incidence of adverse events of 10.70% in Korea. 11 On the other hand, a previous study identifying adverse events using specific ICD-10 codes (Y codes) reported lower incidence (0.20%) than in our results. 28 Although the incidence of adverse events from this study was higher than the figure reported using Y codes, our results seem to be an underestimate compared with a study using medical record review, the criterion standard for evaluating adverse events.…”
Section: Discussioncontrasting
confidence: 89%
“… 19 A recent study using record reviews reported an incidence of adverse events of 10.70% in Korea. 11 On the other hand, a previous study identifying adverse events using specific ICD-10 codes (Y codes) reported lower incidence (0.20%) than in our results. 28 Although the incidence of adverse events from this study was higher than the figure reported using Y codes, our results seem to be an underestimate compared with a study using medical record review, the criterion standard for evaluating adverse events.…”
Section: Discussioncontrasting
confidence: 89%
“…Patient safety, a vital indicator of a quality healthcare delivery system, remains an important issue that plagues many healthcare systems around the world. Despite efforts to curtail and prevent patient safety errors, a wide range of studies conducted across countries suggested that many healthcare systems are vulnerable to these errors and adverse patient events (Kim et al, 2020; Lee & Quinn, 2020). The Institute of Global Health Innovation (2019) reported that these preventable errors have caused approximately 420 million hospitalizations and 5.7 to 8.4 million lives in previous years, as well as massive economic and health concerns in many countries, particularly in underdeveloped and developing regions.…”
mentioning
confidence: 99%
“…This was particularly important in the evaluation of causality and preventability scores in the second-stage review. 4,19 This study attempted to reduce the variations among reviewers in the determination and assessment of adverse events through a 3-stage review conducted by a third 9-member expert review committee with experience in related prior research or activities in the field of patient safety. The incidence rate of adverse events identified in this study was 9.9%, which is similar to the 9.2% reported in a systematic review article.…”
Section: Discussionmentioning
confidence: 99%
“…The type of adverse events was classified into 6 categories, including diagnosis-related, drugs/fluids/blood-related, patient care–related, surgery/procedural-related, infection-related, and other events. The severity was classified into the following 5 levels based on the error classification system used by the National Coordinating Council for Medication Error Reporting and Prevention 16 , 19 : level 1, “events with temporary harm requiring intervention or treatment”; level 2, “events requiring long-term hospitalization treatment”; level 3, “events with permanent harm”; level 4, “events requiring intervention to sustain life”; and level 5, “events contributing to or causing death.”…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation